2021
DOI: 10.26555/ijain.v7i2.677
|View full text |Cite
|
Sign up to set email alerts
|

A particle swarm optimization levy flight algorithm for imputation of missing creatinine dataset

Abstract: Clinicians could intervene during what may be a crucial stage for preventing permanent kidney injury if patients with incipient Acute Kidney Injury (AKI) and those at high risk of developing AKI could be identified. This paper proposes an improved mechanism to machine learning imputation algorithms by introducing the Particle Swarm Levy Flight algorithm. We improve the algorithms by modifying the Particle Swarm Optimization Algorithm (PSO), by enhancing the algorithm with levy flight (PSOLF). The creatinine da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Multi objective approaches Hybrid approaches GA [16]- [18] GP [19] PSO [20] MOGA-II [21]- [22] MOPSO [23] Bayesian ACO+ Bayesian [24] ABC+ Bayesian [25] Max-min ACO +bayesian [26]- [27] Bayesian+ tensor+chaotic PSO [28] Probabilistic GA+KNN [29] GMSA+MPSO+ WKNN [30] PSO+ covariance matrix [32] IDW+TR+ PSO [33] Clustering ACO+ clustering [34] FCM+GA [35][36] FCM+ SVR+GA [37] GA+SOM [38] FCM+PSO [39]- [42] GFM+PSO [43] PSO-ECM+ AAELM [44] ELM+PSO+ FCM [45] PSO+K-means+ ontology [46] SOM+FOA +LSSVM [47] DE+ clustering [48] GA+RF [49] GP+wrapper [55] [56] Neural network GSO+MLP [57] GA+MLP, SA+MLP, PSO+MLP, RF+MLP [58] SC-FITNET [59] SC-FDO+ MLP [60] DL-CS [61] DL-BAT [62] DL-GSA [63] PSO+LSVM [54] PSO+levy flight+SVM [53] MAIS+GA [50] GA+ARO [51] GP+tree vector [52] KNN+LAHC AWOA [31] The proposed approach enhanced imputation for missing multivariate data…”
Section: Single Objective Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…Multi objective approaches Hybrid approaches GA [16]- [18] GP [19] PSO [20] MOGA-II [21]- [22] MOPSO [23] Bayesian ACO+ Bayesian [24] ABC+ Bayesian [25] Max-min ACO +bayesian [26]- [27] Bayesian+ tensor+chaotic PSO [28] Probabilistic GA+KNN [29] GMSA+MPSO+ WKNN [30] PSO+ covariance matrix [32] IDW+TR+ PSO [33] Clustering ACO+ clustering [34] FCM+GA [35][36] FCM+ SVR+GA [37] GA+SOM [38] FCM+PSO [39]- [42] GFM+PSO [43] PSO-ECM+ AAELM [44] ELM+PSO+ FCM [45] PSO+K-means+ ontology [46] SOM+FOA +LSSVM [47] DE+ clustering [48] GA+RF [49] GP+wrapper [55] [56] Neural network GSO+MLP [57] GA+MLP, SA+MLP, PSO+MLP, RF+MLP [58] SC-FITNET [59] SC-FDO+ MLP [60] DL-CS [61] DL-BAT [62] DL-GSA [63] PSO+LSVM [54] PSO+levy flight+SVM [53] MAIS+GA [50] GA+ARO [51] GP+tree vector [52] KNN+LAHC AWOA [31] The proposed approach enhanced imputation for missing multivariate data…”
Section: Single Objective Approachesmentioning
confidence: 99%
“…In [53], Ismail et al incorporated levy flight into PSO to improve global exploration of PSO and helped PSO to escape from local optimum. The results indicated that support vector machine (SVM) imputation, optimized by levy flight PSO achieved the lowest error for filling the incomplete creatinine data than KNN, naïve Bayes, and decision tree imputation.…”
Section: Sc-fitnetmentioning
confidence: 99%
See 2 more Smart Citations
“…Lévy flight is a type of random walk introduced by Paul Lévy in 1937 and has the characteristic of intensive probability in its movement [30]- [33]. Yang, Ting, and Karamanoglu [31] implied that Lévy flight has an excellent capability to explore the search space.…”
Section: Levy Flightmentioning
confidence: 99%